Boma Trials on the Use of the Gregarious-Adult Pheromone Phenylacetonitrile of the Desert Locust Schistocerca gregaria (Forskål, 1775) and Metarhiziumacridum in the Management of Nymphs - Magzoub Omer Bashir; Hassanali, Ahmed; Korena, Haydar Hanan; Bashir, Abdelrahim Widaatalla (University of Khartoum Journal of Agricultural Sciences, 2023)
The trials were conducted within plastic Bomas (10 x10 meters each) in a farm at Sallom (19 38 55 N X 37 15 37 E) 45 kilometers South West of Port Sudan, Sudan. Approximately 1000 fourth instar nymphs of the Desert Locust Schistocerca gregaria (Forskål, 1775) were used per replica in each test. Each test was replicated three times. The treatments included different dosages of Metarhizium acridum alone or incorporated with the Desert Locust gregarious adult pheromone Phenylacetonitrile (PAN). The results indicated that the cumulative mortality rate in day 15 at the end of the tests was 0.994±0.010 with Metarhizium 50 g/ ha. (recommended dose). The rates were 0.991±0.001 and0.967±0.003 with fractional doses of Metarhizium, 25g/ha +PAN and 12g/ha + PAN respectively. When PAN was used alone, the cumulative mortality at day 15 was 0.739 ± 0.017. The same trend in the mortality rate was also evident when the control efficiency was examined. The efficiency in day 15 was 99.32 ± 0.001 with Metarhizium 50 g/ ha. (recommended dose). The rates were 98.75 ±0.056, 96.33±0.30 and 72.78±0.45 with fractional doses of Metarhizium 25g/ha +PAN, 12g/ha +PAN and 6g/ ha +PAN respectively. Control efficiency was 71.82±1.82 and 3.70±1.86 with PAN alone and Diesel respectively. Examination of